2020
DOI: 10.1002/cncr.33233
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid tumors: To treat or not to treat, That is the question

Abstract: Desmoid tumors (DTs) are a rare disease of intermediate malignancy characterized histologically by a locally aggressive, monoclonal, fibroblastic proliferation and clinically by a variable and often unpredictable course. For decades, surgical resection has been the standard initial treatment approach; however, more recently, a paradigm shift toward a more conservative treatment strategy has been introduced. More than 5 years ago, The Desmoid Tumor Working Group started a consensus initiative in Europe with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 29 publications
0
85
0
2
Order By: Relevance
“…Forth, we were not able to compare the event-free survival between first-line observation and medical treatment groups due to the small sample size. Kasper et al stated that a stepwise therapy escalation from an initial, less toxic treatment including observation to more toxic agents seems reasonable for progressive DTs [29]. These limitations should be considered in the analysis of our study results.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Forth, we were not able to compare the event-free survival between first-line observation and medical treatment groups due to the small sample size. Kasper et al stated that a stepwise therapy escalation from an initial, less toxic treatment including observation to more toxic agents seems reasonable for progressive DTs [29]. These limitations should be considered in the analysis of our study results.…”
Section: Discussionmentioning
confidence: 80%
“…According to a recent systematic literature review of active surveillance for patients with DTs, the median follow-up time of the patients was reported in 12 studies and ranged from 8 to 73 months [28]. In the case of subsequent progression or a significant increase in symptom burden, a decision toward treatment may be considered and assessed with at least 3 further assessments and possibly not before 1 year after the initial diagnosis [29]. This study showed poor extremity functional outcomes in the first-line observation/medical treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…Although, for many years, surgery was the standard primary treatment option for desmoid tumors, a more conservative management approach has recently been adopted. The current primary approach is active surveillance, with surgery considered only after failure of medical therapies [1,2]. The benefits of a conservative approach were first identified in two retrospective studies of desmoid tumors.…”
Section: Surgical Abstentionmentioning
confidence: 99%
“…Although this tumour does not metastasise, its potential locally aggressive tumour growth can cause significant morbidity. It is therefore classified as an intermediate tumour by the World Health Organisation [1,2]. The biological behaviour of DTF is unpredictable and displays phases of progressive growth or growth stabilisation and up to 28% of tumours ultimately undergo spontaneous regression [3][4][5].…”
Section: Introductionmentioning
confidence: 99%